2013
DOI: 10.1002/kpm.1421
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Openness in Innovation Processes—A Case Study in the Finnish Food Industry

Abstract: Recent practical business discussion and academic studies highlight the collaborative nature of innovation activities. Today, almost all innovations are generated in cooperation with others in a systemic world. The role of openness is widely acknowledged, but the dynamics of openness in innovation processes is studied and discussed less. There is a lack of understanding about the open and closed phases during innovation processes. By observing such dynamics, this study extends the current theories from the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…They concluded that open innovation mindset means openness, building mutual trust, risk-taking and adaptability to change. A positive attitude toward openness is regarded as a favorable factor for successful open innovation [16,25]. The findings of the research conducted by Engelsberger with a group of scholars [20] evidenced that companies should invest in practices which facilitate developing open innovation mindset among employees.…”
mentioning
confidence: 99%
“…They concluded that open innovation mindset means openness, building mutual trust, risk-taking and adaptability to change. A positive attitude toward openness is regarded as a favorable factor for successful open innovation [16,25]. The findings of the research conducted by Engelsberger with a group of scholars [20] evidenced that companies should invest in practices which facilitate developing open innovation mindset among employees.…”
mentioning
confidence: 99%
“…Recent discussion has highlighted the idea that innovation is more of a dynamic complementary process with integrated feedback loops than a linear set of pre-planned steps to final outcomes (cf. James et al, 2013;Mäkimattila, 2014;Mäkimattila, Melkas & Uotila, 2013;Santoro, Vrontis, Thrassou & Dezi, 2017;Thrassou, Vrontis & Bresciani, 2018a, 2018b): Actions at different levels need to be synchronised. Although grounded in the tasks of individuals, the group initiative is to handle uncertainty related to the tasks and to entrust challenging demands to group processes (Brav, Andersson & Lantz, 2009).…”
Section: Dialectic Approach To Innovation As a Multilevel Dynamic Processmentioning
confidence: 99%
“…The extant innovation literature reinforces the scientific and technological approach at the expense of knowledge innovations. Although, initially, innovation in services has focused on sectors with high economic relevance (such as banking and telecommunications), the study of innovation processes in other sectors (such as in higher education sector, tourism, health and food industry) is only more recent (Consoli and Mina, ; Castro‐Martínez, ; Mäkimattila et al ., ). For instance, researchers contend that we know little about the type of firm characteristics required to promote collaboration between firms and external entities (Belso‐Martínez, ), and there is a paucity of research on the motivations to innovate within service providers such as universities and technology centres (Zhang and Li, ).…”
Section: Introductionmentioning
confidence: 97%